PERSEPSI DAN MINAT SISWA TERHADAP PEMBELAJARAN SENI RUPA DI SMA ADABIAH 2 PADANG - VARADILLA AGUSTI FONDA, Drs. Eswendi, M.Pd., Drs. Yusron Wikarya, M.Pd. (Serupa The Journal of Art Education, 2016)
The purpose of this study were: 1) To describe the students' perceptions of learning in high school art Adabiah 2 Padang, 2) To describe students' interest in learning the art in high school Adabiah 2 Padang. This research is a study using a quantitative approach with descriptive research. Samples were students of class XI SMA Adabiah 2 Courses taken with purposeve sampling techniques. The research data consisted of primary data id taken from the results of questionnaire directly to high school students Adabiah 2 Padang about perception and students' interest in learning the art. Based on research in the field of data processing, the results are as follows; 1) students 'perceptions of learning art is less weel (82.4%), 2) students' interest in learning art is less well (88.0%). That is, the perception and interest of students towards learning in high school art Adabiah 2 Padang overall unfavorable.Keywords: Perception, interests, learning art